Management in the age of digital business complexity - McKelvey, Bill (Abingdon, Oxon New York, NY Routledge, 2021)
"Management in the Age of Digital Business Complexity focuses on how the digital age is changing management and vastly speeding up complexity dynamics. The recent coevolution of technologies has dramatically changed in just a few years how people and firms learn, communicate, and behave. Consequently, the process of how firms coevolve and the speed at which they coevolve has been dramatically changed in the digital age, and managerial methods are lagging way behind. Combining his own expertise with that of a number of specialist and international co-authors, McKelvey conveys how companies that fall behind digitally can quickly be driven out of business. The book has been created for academics seeking to upgrade management thinking into the modern digital age and vastly improve the change capabilities of firms facing digital-oriented competition"--
Managing the consequences of digital networks and accelerated complexity dynamics in digital business ecosystems -- Rescuing economics and management from Darwin's evolution via death-and-replacement by the Baldwin Effect: learning during a lifetime -- Why Lamarck dominates Darwin in explaining organizational change and evolution -- "Simple rules" for improving digital corporate IQ : Basic lessons from complexity science -- Digital dynamic capabilities -- Understanding value conflict between business and society : a new perspective from neuro and complexity sciences -- A digital perspective about how complexity science pushes firms into the stochastic frontier -- Using Crowd wisdom via crowdsourcing : Proof of concept of an efficient digital strategy in the age of digital business complexity.
Includes bibliographical references and index.
Keywords: Organizational change; Electronic commerce -- Management